Massively Multi-Agent Technology AAMAS Workshops, MMAS 2006, LSMAS 2006, and CCMMS 2007 Hakodate, Japan, May 9, 2006 Honolulu, HI, USA, May 15, 2007 Selected and Revised Papers - Jamali, Nadeem; Scerri, Paul.; Sugawara, Toshiharu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book constitutes the thoroughly refereed post-workshop proceedings of the joint AAMAS 2006 International Workshops on Massively Multi-Agent Systems, MMAS 2006, and on Large scale Multi-Agent Systems, LSMAS 2006, held in Hakodate, Japan, in May 2006, and of the International Workshop on Coordination and Control in Massively Multi-Agent Systems, CCMMS 2007, held in Honolulu, HI, USA, in May 2007 as associated event of AAMAS 2007. The 13 revised full papers presented were carefully selected from the presentations made at the 3 workshops fall in 4 broad categories, presenting a snapshot of current research. Included are implementation strategies addressing coordination in the space of spatial and temporal distributed systems; approaches to deal with complexity to make decisions such as task allocation and team formation efficiently, by creating implicit or explicit encapsulations; and finally, a diverse range of applications to which these approaches may be applied, from large-scale agent based simulations to managing different types of networks to image segmentation.
Massively Multi-agent Infrastructure -- A Platform for Massive Agent-Based Simulation and Its Evaluation -- Distributed Coordination of Massively Multi-Agent Systems -- Community-Based Load Balancing for Massively Multi-Agent Systems -- Task Allocation in Massively Multi-agent Systems -- A Study of Coordinated Dynamic Market-Based Task Assignment in Massively Multi-Agent Systems -- Dynamic Pricing Algorithms for Task Allocation in Multi-agent Swarms -- Teams and Organization -- Evolve Individual Agent Strategies to Global Social Law by Hierarchical Immediate Diffusion -- Team Formation Strategies in a Dynamic Large-Scale Environment -- Using Swarm-GAP for Distributed Task Allocation in Complex Scenarios -- Applications of Massively Multi-agent Systems -- Mousetrap 2.0 -- Application of a Massively Multi-Agent System to Internet Routing Management -- An Agent-Based Approach for Range Image Segmentation -- Coordination in Disaster Management and Response: A Unified Approach -- The Scalability of an Environment for Large-Scale Sensor-Networks.
Keywords: Computer science; Computers; Computer Science; Theory of Computation; Computer Science, general; Electronic books